1997
DOI: 10.1177/030006059702500508
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Fluoroquinolone on the Growth and Development of Infants

Abstract: Growth and development were monitored for up to 42 months in nine neonates to whom ciprofloxacin, a fluoroquinolone, was given in the neonatal period at a dosage of 20 mg/kg/day. Ciprofloxacin was used only as a ¿life-saving' therapy in cases of sepsis produced by bacterial agents resistant to other antibiotics. Two other groups of nine neonates, matched by birth weight and gestational age, were studied as controls: one group with sepsis, which was effectively treated with cefotaxime and a group of healthy neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…Radiological confirmation of arthropathy using MR1 was positive in two studies involving six cystic fibrosis patients, who had joint effusions, abnormal thickness of articular cartilage, non-homogeneous structure of cartilage or altered two-layer appearance of cartilage 79 91. In addition to clinical examination and radiological investigation, seven studies (531 cases and 674 controls) investigated the effects of ciprofloxacin on growth of patients after following up the patients for 6–50 months 28 32 33 63 75 109 116. None of these studies found any significant difference in growth of the ciprofloxacin exposed patients compared with the control arm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiological confirmation of arthropathy using MR1 was positive in two studies involving six cystic fibrosis patients, who had joint effusions, abnormal thickness of articular cartilage, non-homogeneous structure of cartilage or altered two-layer appearance of cartilage 79 91. In addition to clinical examination and radiological investigation, seven studies (531 cases and 674 controls) investigated the effects of ciprofloxacin on growth of patients after following up the patients for 6–50 months 28 32 33 63 75 109 116. None of these studies found any significant difference in growth of the ciprofloxacin exposed patients compared with the control arm.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of 23 controlled studies (7 controlled studies were excluded because ciprofloxacin or another fluoroquinolone was administered in the comparator arm) comprising 6481 cases and 17 441 controls showed that there is a 57% increased risk of arthropathy in patients who received ciprofloxacin compared to the comparator arm (OR 1.57, 95% CI 1.26 to 1.97) 13 15–19 2833 63 75 76 79 101 103 105 109 111 112 116. Further analysis of five controlled studies that included only cystic fibrosis patients (227 cases and 391 controls) estimated a 67% increased risk of arthropathy (OR 1.67, 95% CI 1.13 to 2.45) 17 19 79 101 105…”
Section: Resultsmentioning
confidence: 99%
“…A review of three quinolones (ciprofloxacin, ofloxacin, and nalidixic acid) involving over 7,000 children, did not find negative effects on the linear growth of children, however follow-up data (ranging from 1 week to 12 years) are available only for about 500 patients [34]. Another study determined that ciprofloxacin for "life-saving" treatment in infants was safe; no osteoarticular problems or joint deformities were observed at 42 months following administration [35]. Similar evaluations were drawn from the absence of arthropathy during the 4-6 weeks of follow-up of a randomised controlled study in Bangladesh, where single-dose of ciprofloxacin was compared with 12-dose erythromycin for childhood cholera [36].…”
Section: Fluoroquinolonesmentioning
confidence: 99%
“…Gemifloxacin mesylate (GMX), with the chemical name 7-[(4Z)-3-(aminomethyl)-4-methoxyimino-pyrrolidin-1-yl]-1-cyclopropyl-6fluoro-4-oxo-1,8-naphthyridine-3-carboxylic acid methanesulfonate, is a fluoroquinolone antibiotic ( Figure 1) which is mostly used for upper respiratory tract infections [1]. GMX is excreted into breast milk [2].…”
Section: Introductionmentioning
confidence: 99%